PENGARUH PEMBELAJARAN SINEKTIK TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA PAI DI IAI TAFAQQUH FIDDIN DUMAI - Maisuhetni Maisuhetni (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2021)
The main focus of this study was the lowerness of creative thinking ability in PAI students. One strategy that can be implemented to improve PAI students’ creative thinking ability is Synectic Learning. In the learning process, the student’s face with an out of mind problems, give a chance to create a new way when look something, self expression, and approach the problems. The aim of this study was to dercribe the effect of synectic learning through the improving creative thingking ability in PAI students. This study used quasy-experimental design with the non equivalent control group. The students in experimental group have synectic learning while the students in control group have conventional learning. The population of this study was the S1 PAI students of IAI Tafaqquh Fiddin in second semester academic year 2020/2021. The sample taken in this study was done with use purposive sample technique. Among 5 grades, e grade was choosen as the reaserch sample they are grade E as experimental group and grade D as control group. This study used the creative thinking ability test and observation sheet instruments. The data from pretest and posttest result was analyzed quantitatively to find the mean difference of the gain of students’ creative thinking ability in experimental and control groups. According to the data analysis results obtain that the average of normalized-gain in experimental group with synectic learning was significantly better than that the average of normalized-gain control group with conventional learning.